Converter control method without AC voltage sensor during asymmetric network voltage - WANG LINGLING; GONG WENMING; HU SHUJU (2017)
The invention discloses a converter control method without an AC voltage sensor during the asymmetric network voltage. The method comprises the steps: firstly building a quadrature filter for the no-difference following characteristics of an AC signal with the specific frequency through employing a second-order generalized integrator, and building a voltage observer of a three-phase grid-connected inverter under the condition of the asymmetric network voltage through employing the quadrature filter; firstly taking a measured power grid side current signal and an output bridge end reference signal of an inverter controller as the input of the voltage observer in a two-phase static coordinate system, and carrying out the observation of the network voltage; thirdly carrying out the positive and negative separation based on the output quantity of the quadrature filter, thereby enabling the positive and negative separation and the network voltage observation to be carried out synchronously; finally combining with